Influence of comorbidity with depression on interdisciplinary therapy: outcomes in patients with chronic low back pain - Wang, Haili; Ahrens, Carsten; Rief, Winfried; Schiltenwolf, Marcus (Arthritis Research & Therapy, 2010)
Our previous work showed higher tumour necrosis factor (TNF)-α levels in patients with chronic low back pain (cLBP) compared to healthy controls. However, patients with depression as a comorbidity did not have higher TNF-α levels in comparison to patients without depression. In this study we investigated the influence of depression on therapy outcomes such as TNF-α serum levels, pain intensity and back function in patients with cLBP. Our hypothesis was that patients with both cLBP and depression benefit no less than patients with cLBP alone from the multidisciplinary pain therapy.